The role of lenvatinib in the era of immunotherapy of hepatocellular carcinoma - Matthew Man Pok Lee; Landon Long Chan; Stephen Lam Chan (Korean Liver Cancer Association, 2023)
Hepatocellular carcinoma (HCC) frequently presents as advanced stage with poor prognosis and high mortality. Systemic treatment is the treatment of choice for advanced disease. In 2007, the first multi-kinase inhibitor (MKI) sorafenib was approved and shown to modestly prolong overall survival (OS). The progress of systemic therapy has been slow afterwards until 2018 when lenvatinib, another MKI, was shown to be non-inferior to sorafenib on median OS as the first-line therapy for HCC. Since then, remarkable progress has been achieved on the treatment of advanced HCC, including the development of second-line targeted treatment, including regorafenib, cabozantinib and ramucirumab from 2017 to 2019. A growing focus has been placed on immune checkpoint inhibitors (ICIs) targeting programmed cell death-1 (PD-1), its ligand PD-L1, and cytotoxic T-lymphocyte-associated protein 4. These ICIs have proven their potency in treating HCC as both initial and subsequent line of therapy. At present, both regimens of atezolizumab combined with bevacizumab, as well as the combination of tremelimumab and durvalumab, are recommended as the first-line treatments based on positive phase III clinical trials. With the advancement of ICIs, it is anticipated that the role of MKIs in the treatment of HCC will evolve. In this article, lenvatinib, one of the most commonly used MKIs in HCC, is chosen to be reviewed.